2020
DOI: 10.1108/ijcma-06-2019-0092
|View full text |Cite
|
Sign up to set email alerts
|

Handling inter-organisational conflict based on bargaining power

Abstract: Purpose This paper aims to reveal the effects of an organisation’s bargaining power on its negotiating behaviours (including integrating, obliging, compromising, dominating and avoiding) in the context of inter-organisational conflict in construction projects and investigate how organisational power distance orientation moderates the relationship between the organisation’s bargaining power and its negotiating behaviours. Design/methodology/approach The authors conducted a questionnaire survey among practitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 63 publications
3
9
0
Order By: Relevance
“…Another notable result concerns the higher scores for relationship conflict reported by Romanian groups as compared to the Dutch ones. To some extent, these results are aligned with the ones reported by Lu, Wei and Wang (2020) showing that high power asymetry is associated with increased relationship conflict. It is likely that Romanian groups operate in organizations in which power asymetry is higher than in Dutch organizations, and such concentration of power could trigger more relationship conflict.…”
Section: Discussionsupporting
confidence: 83%
“…Another notable result concerns the higher scores for relationship conflict reported by Romanian groups as compared to the Dutch ones. To some extent, these results are aligned with the ones reported by Lu, Wei and Wang (2020) showing that high power asymetry is associated with increased relationship conflict. It is likely that Romanian groups operate in organizations in which power asymetry is higher than in Dutch organizations, and such concentration of power could trigger more relationship conflict.…”
Section: Discussionsupporting
confidence: 83%
“…Chinese culture is characterized by collectivism, high power distance, and long-term orientation. Under the influence of such a culture, the transaction parties attach great importance to solidarity and long-term relationships in the transaction (Lu et al, 2020). When the owner’s status is high, the contractor tends to comply with the owner’s instructions without revolt and regard these instructions as the PBO’s legitimate power.…”
Section: Discussionmentioning
confidence: 99%
“…This has tended to focus on either third-party intervention by managers in subordinate conflicts (Kozan et al, 2007;Kozan et al, 2014) or conflict avoidance between subordinates and their managers (Tjosvold and Sun, 2002;Wang, 2006;Xu, 2009). The majority of the research focuses on the Chinese (Xu, 2009;Tjosvold and Sun, 2002;Lu et al, 2020) or Turkish context (Kozan et al, 2007;Kozan et al, 2014), with one additional study looking at comparative differences in conflict avoidance between Chinese and American participants (Friedman et al, 2006). Looking more closely at this research, in the Turkish context, research has explored managers' intervention in subordinate conflicts within Turkish organizations.…”
Section: Organizational Outflanking As a Methods Of Conflict Avoidancementioning
confidence: 99%
“…It was shown that third parties play a significant role in preserving the face of adversaries. Looking at another collectivist culture, Lu et al (2020) similarly suggest that those from a low-power party may adopt outflanking as a strategy for avoiding conflict rather than resolving the disagreement immediately. The study highlighted how in the Chinese context, negotiators in the low-power party may try to interact with superiors to request intervention to resolve conflicts.…”
Section: Organizational Outflanking As a Methods Of Conflict Avoidancementioning
confidence: 99%